1.3‐µm buried‐heterostructure VCSELs with GaAs/AlGaAs metamorphic DBRs grown by MOCVD. Issue 2 (1st January 2020) - Ohiso, Y.; Sato, T.; Shindo, T.; Matsuzaki, H.
Abstract : The authors report buried‐heterostructure long‐wavelength VCSELs with GaAs/AlGaAs metamorphic DBRs, which has a potential for low thermal resistance and operation in the single transverse mode with a large emission area. In spite of their being upside‐up and unmounted, they achieve CW operation at 17°C, and VCSELs with a 15‐µm mesa exhibit single‐mode operation.